Knee osteoarthritis associated with different kinds of amyloid deposits and the impact of aging on type of amyloid. (2nd January 2016) - Yanagisawa, Akihiro; Ueda, Mitsuharu; Sueyoshi, Takanao; Nakamura, Eiichi; Tasaki, Masayoshi; Suenaga, Genki; Motokawa, Hiroaki; Toyoshima, Risa; Kinoshita, Yumiko; Misumi, Yohei; Yamashita, Taro; Sakaguchi, Mitsuru; et al.
Abstract: Amyloidosis is a protein conformational disorder in which amyloid fibrils accumulate in the extracellular space and induce organ dysfunction. Recently, two different amyloidogenic proteins, transthyretin (TTR) and apolipoprotein A-I (Apo A-I), were identified in amyloid deposits in knee joints in patients with knee osteoarthritis (OA). However, clinicopathological differences related to those two kinds of amyloid deposits in the knee joint remain to be clarified. Here, we investigated the clinicopathological features related to these knee amyloid deposits associated with knee OA and the biochemical characteristics of the amyloid deposits. We found that all of our patients with knee OA had amyloid deposits in the knee joints, especially in the meniscus, and those deposits were primarily derived from TTR and/or Apo A-I. Some patients with knee OA, however, had unclassified amyloid deposits. One of our interesting observations concerned the different effects of aging on each type of amyloid formed. The frequency of formation of ATTR deposits clearly increased with age, but that of AApo A-I deposits decreased. Furthermore, we found that ∼16% of patients with knee OA developed ATTR/AApo A-I double deposits in the meniscus. Amyloid deposition may therefore be a common histopathological feature associated with knee OA. Also, aging may induce ATTR formation in the knee joint in elderly patients with knee OA, whereas AApo A-I formation may be inversely correlated with age.